PENERAPAN MODEL PROJECT BASED LEARNING DALAM KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR NEGRI SIDOREJO 02 - Rindra Guseva, Praditya; Suswandari, Meidawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of the Project Based Learning (PjBL) model in improving the critical thinking skills of fourth-grade students in the science subject at Sidorejo 02 Elementary School. This study uses a qualitative approach with a descriptive type. The research subjects consisted of fourth-grade students and the class teacher as the learning implementer. The subject determination was done purposively. Data were collected through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. Critical thinking skills were analyzed based on indicators of identifying problems, analyzing information, expressing opinions with logical reasons, drawing conclusions, and reflecting on project results. The results showed that the implementation of PjBL had a positive impact on students' critical thinking skills. Through systematic learning stages, students were more active in asking questions, discussing, collaborating, solving problems, and presenting project results in a coherent manner. In addition, student motivation and enthusiasm increased during the learning process. Despite obstacles such as time constraints and lack of student focus, overall the PjBL model was effective in creating meaningful learning and was able to have a positive impact on elementary school students' critical thinking.